Fucoidan : Manfaat dalam Industri Peternakan - Yanuartono Yanuartono; Alfarisa Nururrozi; Hary Purnamaningsih; Soedarmanto Indarjulianto; Slamet Raharjo (Jurnal Sain Veteriner, 2018)
Research of interest marine algae and seagrasses have been renewed, because they are considered to be promising resources of functional ingredients in the development of novel products. Fucoidans are a class of fucose-rich sulfated carbohydrates found in brown marine algae and echinoderms, and more recently identified in seagrasses. Chemical compositions of most fucoidans are complex, mainly being composed of fucose and sulfate. They also contain other monosaccharides like mannose, galactose, glucose, xylose and uronic acids, even acetyl groups and protein and it’s have potential therapeutic properties, including anti-viral activity. Currently, fucoidans are available for use in therapeutic and dietary supplements for inclusion in pet, livestock and aquaculture feed supplements. This review summarizes experimental evidence indicating that Fucoidan can improve the quality of feed ingredients for livestock, pets and aquaculture to improve health.